Can Delivery Dialysis Dose Affect Survival of Acute Kidney Injury Patients? - Gera Abrao, Juliana Maria [UNESP]; Ponce, Daniela [UNESP]; de Brito, Germana Alves [UNESP]; Balbi, André Luis [UNESP] (Informa Healthcare, 2012)
Intensity of dialysis dose in acute kidney injury (AKI) might benefit critically ill patients. The aim of this study was to evaluate the effect of intermittent hemodialysis (IHD) dose on mortality in patients with AKI. Methods: Prospective observational study was performed on AKI patients treated with IHD. The delivered dialysis dose per session was calculated based on single-pool Kt/V urea. Patients were allocated in two groups according to the weekly delivered median Kt/V: higher intensity dialysis dose (HID: Kt/V higher than median) and lower intensity dialysis dose (LID: Kt/V lower than median). Thereafter, AKI patients were divided according to the presence or absence of sepsis and urine output. Clinical and lab characteristics and survival of AKI patients were compared. Results: A total of 121 AKI patients were evaluated. Forty-two patients did not present with sepsis and 45 did not present with oliguria. Mortality rate after 30 days was lower in the HID group without sepsis (14.3% x 47.6%; p = 0.045) and without oliguria (31.8% x 69.5%; p = 0.025). Survival curves also showed that the HID group had higher survival rate when compared with the LID group in non-septic and non-oliguric patients (p = 0.007 and p = 0.003, respectively). Conclusion: Higher dialysis doses can be associated with better survival of less seriously ill AKI patients.
Keywords: dialysis dose; hemodialysis; acute kidney injury; low urine output; sepsis; survival